Harnessing Wordwall for Enhanced Vocabulary Acquisition and Engagement in Non-Formal Elementary Education - Arsyad, Muhammad (JOLLT Journal of Languages and Language Teaching, 2024)
This study explored the effectiveness of the Wordwall application in enhancing vocabulary acquisition and engagement among students in non-formal educational settings. A qualitative case study approach was employed, involving semi-structured interviews with 16 students. The research investigated students' perceptions of Wordwall, focusing on its interactive features and their impact on motivation and learning outcomes. Findings revealed that Wordwall significantly increases student engagement by providing a dynamic and visually stimulating learning environment. Wordwall features and multimedia elements make vocabulary learning more enjoyable, which helps maintain student interest and facilitates better vocabulary retention. However, challenges such as difficulties with longer questions and unfamiliar vocabulary were noted, indicating areas where instructional design could be improved. This study highlighted the importance of incorporating interactive digital tools in non-formal education to enhance vocabulary learning. It suggested that Wordwall innovative approach can address the unique challenges faced by students, promoting more effective and engaging vocabulary acquisition. The research contributed valuable insights into the role of digital technologies in non-traditional educational contexts, emphasizing the need for adaptive learning tools that cater to diverse learning styles and cognitive levels, ultimately fostering a more inclusive and effective learning environment.